In Transgenic Erythropoietin Deficient Mice, an Increase in Respiratory Response to Hypercapnia Parallels Abnormal Distribution of CO2/H+-Activated Cells in the Medulla Oblongata - Jeton, Florine; Perrin-Terrin, Anne-Sophie; Yegen, Celine-Hivda; Marchant, Dominique; Richalet, Jean-Paul; Pichon, Aurélien; Boncoeur, Emilie; Bodineau, Laurence; Voituron, Nicolas (Frontiers in Physiology, 2022)
Erythropoietin (Epo) and its receptor are expressed in central respiratory areas. We hypothesized that chronic Epo deficiency alters functioning of central respiratory areas and thus the respiratory adaptation to hypercapnia. The hypercapnic ventilatory response (HcVR) was evaluated by whole body plethysmography in wild type (WT) and Epo deficient (Epo-TAgh) adult male mice under 4%CO2. Epo-TAgh mice showed a larger HcVR than WT mice because of an increase in both respiratory frequency and tidal volume whereas WT mice only increased their tidal volume. Functional histological approach revealed changes in CO2/H+-activated cells between Epo-TAgh and WT mice. First, Epo-TAgh mice showed a less important hypercapnic increase in c-FOS-positive number of cells in the retrotrapezoid nucleus/parafacial respiratory group than WT, and this, independently of changes in the number of PHOX2B-expressing cells. Second, we did not observe in Epo-TAgh mice the hypercapnic increase in c-FOS-positive number of cells in the nucleus of the solitary tract present in WT mice. Finally, whereas hypercapnia did not induce an increase in the c-FOS-positive number of cells in medullary raphe nuclei in WT mice, chronic Epo deficiency conduced to the observation of hypercapnic activated cells in raphe pallidus and magnus nuclei, with an important part of c-FOS positive cells displaying an immunoreactivity for serotonin in the raphe pallidus nucleus. All of these elements suggest that chronic Epo-deficiency affects both the pattern of ventilatory response to hypercapnia and associated medullary respiratory network at adult stage with an increase in the sensitivity of 5-HT and non-5-HT neurons of the raphe medullary nuclei leading to stimulation of fR for moderate level of CO2.